Multiuser adaptive subcarrier-and-bit allocation with adaptive cell selection for OFDM systems. - Ying Jun Zhang (IEEE Transactions on wireless communications)
Adaptive resource allocation has been identified as one of the key technologies for providing efficient utilization of the limited power and spectrum in future wireless systems. In this paper, an adaptive resource allocation methodology is proposed for cellular orthogonal frequency division multiplexing systems in a multiuser environment. The proposed method is featured as a low-complexity algorithm that involves not only adaptive modulation, but also adaptive multiple-access control and cell selection. Specifically, a multiuser subcarrier-and-bit loading scheme is developed to maximize the spectral efficiency. Besides, a dynamic cell selection scheme is proposed to deal with the problem of overloading and nonuniform traffic density. Numerical results show that the presented algorithm offers significant improvement in spectral efficiency due to the successful exploitation of channel variation, multiuser diversity, and inter-cell diversity.